2013
DOI: 10.1158/0008-5472.can-12-3022
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast-Specific Protein 1/S100A4–Positive Cells Prevent Carcinoma through Collagen Production and Encapsulation of Carcinogens

Abstract: Stromal restraints to cancer are critical determinants of disease but they remain incompletely understood. Here, we report a novel mechanism for host surveillance against cancer contributed by fibroblast-specific protein 1 (FSP1) þ / S100A4 þ fibroblasts. Mechanistic studies of fibrosarcoma formation caused by subcutaneous injection of the carcinogen methylcholanthrene (MCA) had suggested that IFN-g receptor signaling may restrict MCA diffusion by inducing expression of collagen (foreign body reaction). We tes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 45 publications
(60 reference statements)
1
48
0
Order By: Relevance
“…Those of PDGFRβ type are thought to be associated with metastatic spread [25] and high interstitial fluid pressure [26]. S100A4 (FSP-1)-type CAFs, which were highly expressed in breast cancer with fibrous stroma in our study, have been suggested to associate with metastatic colonization [27], macrophage infiltration [28], and protection from carcinogens [29]. There are several possible explanations for the differential expression of CAFrelated proteins between breast cancer with fibrous and adipose stroma.…”
Section: Discussionmentioning
confidence: 58%
“…Those of PDGFRβ type are thought to be associated with metastatic spread [25] and high interstitial fluid pressure [26]. S100A4 (FSP-1)-type CAFs, which were highly expressed in breast cancer with fibrous stroma in our study, have been suggested to associate with metastatic colonization [27], macrophage infiltration [28], and protection from carcinogens [29]. There are several possible explanations for the differential expression of CAFrelated proteins between breast cancer with fibrous and adipose stroma.…”
Section: Discussionmentioning
confidence: 58%
“…S100A4, also known as fibroblast-specific protein 1, is a member of the S100 calcium-binding protein family and was first cloned in metastatic cells and fibroblasts [13,14]. It is expressed in various cell types, including fibroblasts, macrophages and tumor cells [15][16][17][18][19][20]. S100A4 was reported to be intracellular, or secreted as a normal cytokine, and it plays important roles in tumor cell survival and metastasis [19,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…17 , 18 Previous studies have reported that S100A4 is expressed in a variety of cells, such as fibroblasts, macrophages, and malignant cells, and plays a crucial role in mediating tumor-stromal interplay. 19-23 S100A4 functions as both intracellular and extracellular forms. 24 , 25 Intracellular S100A4 is involved in a wide range of biological functions, such as the regulation of angiogenesis, cell survival, motility, invasion or metastasis.…”
Section: Introductionmentioning
confidence: 99%